The competences of eProfessionals to use in social and health care - Jauhiainen, Annikki; Sihvo, Päivi; Hämäläinen, Susanne; Hietanen, Aija; Nykänen, Jaana; Hämäläinen, Jaana; Franssila, Päivi; Tikkanen, Kaija (Finnish Journal of eHealth and eWelfare, 2020)
Digital technology changes the work in the field of social and health care as well as customer services and therefore, the competence required of professionals in the field. The DigiSote projects (ESF) in North Karelia and Northern Savonia developed digital social and health care services and the related competence of professionals in the field. The concept of eProfessional was created within the project. The purpose of the development work was to describe the need for eProfessionals as well as the duties and competence of eProfessionals in social and health care. Quick experiments and workshops were used as the development method in the project. The aim of the experiments was to develop social and health care services and to recognise the competence needs required by digitalisation. The materials for defining the competence of eProfessionals included material obtained from future workshops (n = 3) and training workshops (n = 3) as well as digital service pilot reports (n = 7), thematic interviews (n = 17) for public, private and third sector managers in the field of welfare, and expert evaluations (n = 35) on the fields of competence and competence requirements. Besides the social and health care professionals, clients, ICT professionals, social and health care teachers and representatives of other projects (n = 73) participated in the future workshops. The training workshops were attended by social and health care professionals and supervisors (n = 70). The text-based material was analysed by inductive content analysis. In the expert evaluation, the respondents evaluated the relevance of competence requirements and provided suggestions for improving them. The competence of eProfessionals was seen as special competence consisting of eight areas of competence and 34 competence requirements. The areas of competence and the competence requirements were used to develop an eProfessional’s competence map for evaluating the competence. eProfessionals develop both work and the digital services within their organisations and guide, counsel and support the clients and professionals in using digital services. Part of social and health care professionals need training to become eProfessionals. Modular, supplementary training enables the development of need-based and work-related competence towards becoming an eProfessional.